UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN MODEL PEMBELAJARAN INKUIRI PADA MATA KULIAH KONSEP DASAR IPA 2 DI PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR TAHUN AKADEMIK 2013/2014 - Mahmud Alpusari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
In line with the competency-based curriculum at the University of Riau, the effort to improvelearning basic concepts of science 2 courses puts emphasis on understanding the concept ofmatter, which is based on students' learning activities through scientific inquiry.Implementation of action research consists of two cycles in PGSD JIP University of Riau onthe odd semester of 2013/2014 with 55 third semester students. Based on the research results,lecturing process by applying the model of inquiry learning, students’ activity increased inwhich in the first cycle all activities are good category except activity I and II are faircategory. Meanwhile students’ activity in first and fourth in cycle II is good category, andvery good category in second, third, fifth, and sixth activity. Temporarily student’s learningoutcomes increased from pre-tests with an average65.45 into 77,0 in daily test I and 77.45onthe daily test II. Improvement from initial data to the first cycle was 11.55, while the datafrom the beginning to the second cycle increased 12 points. In general the improvement ofstudents’learning is possible because the learning model used is inquiry learning so thatlearning becomes active which centered into students by presenting a problem, then studentsare asked to carry out a simple experiment using equipment and tools, using data, arrangingreports, communicating the results of observations based on concepts and learned principles.Keywords: Inquiry, students’ activity, learning outcomes.